Writing About Emotional Experiences as a Therapeutic Process - Pennebaker, James W. (Psychological Science, 1997)
For the past decade, an increasing number of studies have demonstrated that when individuals write about emotional experiences, significant physical and mental health improvements follow The basic paradigm and findings are summarized along with some boundary conditions Although a reduction in inhibition may contribute to the disclosure phenomenon changes in basic cognitive and linguistic processes during writing predict better health Implications for theory and treatment are discussed